Study on Blasting Characteristics of Soft-Hard Rock Strata Based on Energy Fields and Particle Expansion Loading Algorithm - Jianbin Cui; Liangfu Xie; Yongjun Qin; Xuejun Liu; Wei Qiao; Zeyu Hu; Liming Wu; Liewang Qiu; Ke Huang (Geofluids)
Complex geological conditions often make the blasting effect difficult to control. In order to explore the influence of soft-hard rock strata on rock blasting characteristics, based on PFC2D software, combined with particle expansion loading algorithm, the numerical simulation blasting experiments are carried out. Firstly, the rationality of blasting method is verified by single-hole sandstone blasting experiment. Then, the soft-hard composite strata are established, and the single-hole blasting experiments of composite strata, with different distribution thickness of soft rock stratum and hard rock stratum, are carried out. The experimental results are analyzed from three perspectives: crack network state, internal stress of rock mass, and energy field. Results show that (i) the distance between the interface of soft-hard rock and the blasthole seriously affects the blasting effect. The law of crack number varying with the distance is obtained through further analysis. (ii) When detonated in the hard rock, if the structural plane is about 2 times the radius of crushing area from blasthole, the rock mass will be in a relatively high stress state due to the reflection and superposition of stress waves. (iii) When detonated in the hard rock, if the structural plane is about 2 times the radius of crushing area from blasthole, compared with pure hard rock case, the peak kinetic energy and peak friction energy are increased by about 15 times and 2.6 times, respectively, and the peak strain energy is attenuated by 18%.